Accuracy and Trending Ability of Electrical Biosensing Technology for Non-invasive Cardiac Output Monitoring in Neonates: A Systematic Qualitative Review - Van Wyk, Lizelle; Gupta, Samir; Lawrenson, John; de Boode, Willem-Pieter (Frontiers in Pediatrics, 2022)
Background: Electrical biosensing technology (EBT) is an umbrella term for non-invasive technology utilising the body’s fluctuating resistance to electrical current flow to estimate cardiac output. Monitoring cardiac output in neonates may allow for timely recognition of hemodynamic compromise and allow for prompt therapy, thereby mitigating adverse outcomes. For a new technology to be safely used in the clinical environment for therapeutic decisions, it must be proven to be accurate, precise and be able to track temporal changes. The aim of this systematic review was to identify and analyze studies that describe the accuracy, precision, and trending ability of EBT to non-invasively monitor Left ventricular cardiac output and/or stroke volume in neonates. Methods: A qualitative systematic review was performed. Studies were identified from PubMed NCBI, SCOPUS and EBSCOHost up to November 2021, where EBT technologies were analyzed in neonates, in comparison to a reference technology. Outcome measures were bias, limits of agreement, percentage error for agreement studies and data from 4-quadrant and polar plots for trending studies. Effect direction plots were used to present results. Results: Fifteen neonatal studies were identified, 14 for agreement and 1 for trending analysis. Only thoracic electrical biosensing technology (TEBT), with transthoracic echocardiography (TTE) as the comparator, studies were available for analyzes. High heterogeneity existed between studies. An equal number of studies showed over- and underestimation of left ventricular output parameters. . All studies showed small bias, wide limits of agreement, with most studies having a percentage error >30%. Sub-analyses for respiratory support mode, cardiac anomalies and type of technology showed similar results. The single trending study showed poor concordance, high angular bias, and poor angular concordance. Discussion: Overall, TEBT shows reasonable accuracy, poor precision, and non-interchangeability with TTE. However, high heterogeneity hampers proper analysis. TEBT should be used with caution in the neonatal population for monitoring and determining therapeutic interventions. The use of TEBT trend monitoring has not been sufficiently studied and requires further evaluation in future trials.